Same Book, Different Bookmarks: The Development and Preliminary Validation of the Bible Verse Selection Task as a Measure of Christian Fundamentalism. Issue 4 (December 2019) - Rouse, Steven V.; Haas, Heather A.; Lammert, Brian C.; Eastman, Kyle D.
The development and preliminary validation of a new measure of Christian fundamentalism required a multi-stage process. In an initial exploratory study, participants indicated which of a set of Bible verses were most central to their faith, and factor analysis was used to identify verses that appeared to tap a latent dimension of religious fundamentalism (Study 1). These relationships were retested with a new method in a new sample (Study 2), and the items that predicted fundamentalism in both samples were incorporated into a new measure of Christian fundamentalism, the Bible Verse Selection Task (BVST). The forced-choice format of the BVST may be less impacted by social desirability response styles that may affect scores on existing fundamentalism scales (Studies 3 and 4) while preserving useful levels of criterion-related validity (Study 5) and convergent evidence of construct validity (Study 6). These studies provide initial psychometric evidence for the BVST as an internally consistent measure of Christian fundamentalism that predicts scores on other fundamentalism scales and related constructs including traditionalism, authoritarianism, and political conservativism.